Gastrointestinal characterisation and drug solubility determination in animals. (5th January 2015) - Merchant, Hamid A; Afonso-Pereira, Francisco; Rabbie, Sarit C; Youssef, Sandy A; Basit, Abdul W
Abstract: Objectives: To characterise the gastrointestinal (GI) environment in rat, rabbit and pig for the purpose of determining their utility as animal models for drug delivery in humans. Methods: GI fluid samples were characterised for osmolality, surface tension, pH and buffer capacity. The solubility of two model drugs, mesalazine (ionisable) and prednisolone (unionisable), were also measured and the results were correlated to the physicochemical fluid data. Key findings: The solubility of the ionisable drug mesalazine was positively correlated to the GI pH in all three species and was significantly influenced by the pH difference. In contrast, the solubility of the unionisable compound prednisolone was not correlated significantly to the changes in pH, buffer capacity, osmolality or surface tension. In general, the solubility of prednisolone was constant irrespective of the location of the sample in the gut from rabbit and pig; however, an unusual trend was observed for the solubility of prednisolone in rats. Conclusions: The results suggest that solubility of ionisable drugs or pH-responsive formulations is significantly influenced by the differences in pH along the GI tract and inter-species differences. It was also found that the data on the GI solubility of prednisolone (a neutral compound) in rats might overestimate its true value in humans.